GAMBARAN PENGETAHUAN IBU YANG MEMPUNYAI BALITA TENTANG STUNTING PADA BALITA DI DUSUN DONDONG TIMUR II DESA STABAT LAMA BARAT KECAMATAN WAMPU KABUPATEN LANGKAT TAHUN 2018 - musdalina - (STIKes Mitra Husada Medan, 2019)
Indonesia ranks 17th highest among 117 countries in the world that have stunting problems with a prevalence of 37.2%. In North Sumatra Province in particular Langkat Regency in 2013 the prevalence of stunting was 55.48%.This research is descriptive using primary data in the form of questionnaires for mothers who have toddlers in Dondong Timur II Hamlet, Stabat Lama Barat Village, Wampu Subdistrict, Langkat Regency in 2018. The population in this study were 30 mothers of infants with a technique total population.The results showed that the majority of mothers' lack of knowledge regarding the definition of stunting was 66.6%, about the causes of stunting 43.3%, stunting symptoms 53.4%, the impact of stunting 50%, and prevention of stunting by 46.7%.In general, respondents' knowledge about stunting is still lacking. It is hoped that policy makers should create policies with a primary focus on prevention of stunting, for mothers who have toddlers should be diligent in seeking information about stunting by bringing toddlers to the posyandu.Keywords: Knowledge, Stunting, Toddler